Acousto-Optic Marker for Determining the Weight and Center of Gravity of the Aircraft - Agayev, E.A. (Herald of Azerbaijan Engineering Academy, 2021)
The article shows the application of a new method for determining the center of gravity and weight of the aircraft and the process of its implementation. For this purpose, using the acousto-optic marker is measured displacement of the front and rear sides of the fuselage and is determined the center of gravity and weight on the basis of the obtained values. The method is synthesized on the basis of an acousto-optic modulator operating in Bregg diffraction mode. The distance determined by the laser rangefinder is used as the support parameter. Based on the support parameter is formed a high-precision measurement marker perpendicular to it.